(3GdbGfhf GdOhdj GdYGe aj KhHg GdLOjOs - (3QTGO YGQa(B, (3GdSjOs ((3YeGf(B:s (3OGQ hGFd ddfTQ(B,s, 2001)
(3YehejGJ aj GdJYQja HbGfhf GdOhdj GdYGe, eUGOQ GdbGfhf GdOhdj GdYGe, GdTNUjI GdbGfhfjI GdOhdjI, GdeSDhdjI GdOhdjI, GdhSGFd GdSdejI dJShjI GdefGRYGJ GdOhdjI, GdaQO aj GdbGfhf GdOhdjs
Keywords: (3GdbGfhfs; (3GdbGfhf GdOhdjs; (3GdefGRYGJ GdOhdjIs